THE UKRAINIAN PATH TO EUROPE IN THE KHERSON PRESS DURING THE PERIOD OF GERMAN-NAZI OCCUPATION 1941–1943 (BASED ON THE MATERIALS OF THE NEWSPAPER “VOICE OF THE DNIPRO”) (Південний архів (історичні науки), 2022)
The purpose of the work is to analyze the materials of the Kherson newspaper “Holos Dnipra” (“Voice of the Dnipro”) during the German-Nazi occupation, which reflected the position of the figures of the Ukrainian national movement regarding the direction of the European path of Ukraine’s development. Research results. In the process of analyzing the nature of the activities of Kherson’s Ukrainian legal press during the period of Hitler’s occupation, it is necessary to emphasize certain features on the example of the newspaper “Voice of the Dnipro”. The creation of the Ukrainian national media resource was aimed at getting ahead of the Germans in the formation of the information doctrine in the region and ensuring minimal intervention of the occupation authorities in the editorial policy. This, as well as the subsequent fate of the members of the editorial board, does not give grounds to consider their information policy and activity as collaborative. Since the editorial policy was formed under the influence of the representatives of the Kherson branch of the Organization of Ukrainian Nationalists, who were natives of the western Ukrainian regions and residents of the Kherson region, which suffered from the Soviet repressive machine, the nature of newspaper publications was characterized by a fairly unambiguous attitude to the communist regime. Their consideration of the prospects for the formation of the European model in the process of national state-building took place, on the one hand, under the significant influence of the German image of the new Europe, and on the other hand, according to the not quite positive for Ukrainians experience of relations with the leading democratic countries of the West in the first quarter of the 20th century. Conclusions. The analysis of the printed material on the pages of “Voice of the Dnipro” makes it possible to assert that, despite the intense pressure of the German administration regarding the clearly defined nature of the information content and official coloring, the representatives of the Ukrainian editorial offices had the main goal of spreading the national idea of the state, conceptually close to state models of the European type. Thus, the focus of the Ukrainian national statist concept on the western path of development and Ukraine’s obtaining a worthy place in the European system of relations is clearly visible in the publications of the Kherson “Voice of the Dnipro”.
Keywords: local press, “Voice of the Dnipro”, Organization of Ukrainian Nationalists, Kherson